Cloning and expression of xylanase 10 from Cryptovalsa mangrovei (BCC7197) in Pichia pastoris: FULL LENGTH RESEARCH PAPER - Boonyapakron, Katewadee; Pootanakit, Kusol; Chantasingh, Duriya; Kirtikara, Kanyawim; Eurwilaichitr, Lily (DNA sequence, 2005)
Xylanases are one of the industrially valuable enzymes. Using RT-PCR and 5′- and 3′-RACE procedures, we have cloned a full-length xylanase encoding gene from a filamentous fungus, Cryptovalsa mangrovei (BCC7197) from Phuket, Thailand. The results showed that BCC7197 xylanase cDNA has an open reading frame of 978 bp encoding 325 amino acid residues. Further sequence analysis revealed that this xylanase gene is belonged to the glycosyl hydrolase family 10 and has ∼50-60% amino acid sequence similarity to other fungal xylanases. Furthermore, expression of BCC7197 xylanase in the Pichia pastoris was also performed. The results demonstrated that the active BCC7197 xylanase protein was successfully produced and secreted from P. pastoris.